The Use of Taboo Words in The Bad Boys II Movie - Ayu Asmidah; Jepri Jepri; Rosmiati Rosmiati (Faculty of Letters Universitas Balikpapan, 2021)
This research aims to analyze taboo words in the Bad Boys II movie. The objective of this research is to identify the types of taboo words that are mostly found in the Bad Boys II movie. The theory used in this research is Sociolinguistics by Wardhaugh theory of types of taboo words. The methodology employed is qualitative approach specifically is used in this research, with the researcher as the main instrument to collect data in form of dialogue from Bad Boys II by watching the movie repeatedly and the researcher analyzes and interprets the data to reach based on the taboo words and its functions proposed by Wardhaugh. The findings of the research are dominated by bodily functions; the numbers of the data is ten data, the others are religious matters, and certain game animals, the first is eight data and the letter is three data those taboo eight words provoke a chaotic reaction.